Engineering tissue‐specific blood vessels - Lauren A. Herron; Corey S. Hansen; Hasan E. Abaci (Wiley, 2019)
Abstract Vascular diversity among organs has recently become widely recognized. Several studies using mouse and human fetal tissues revealed distinct characteristics of organ‐specific vasculature in molecular and functional levels. Thorough understanding of vascular heterogeneities in human adult tissues is significant for developing novel strategies for targeted drug delivery and tissue regeneration. Recent advancements in microfabrication techniques, biomaterials, and differentiation protocols allowed for incorporation of microvasculature into engineered organs. Such vascularized organ models represent physiologically relevant platforms that may offer innovative tools for dissecting the effects of the organ microenvironment on vascular development and expand our present knowledge on organ‐specific human vasculature. In this article, we provide an overview of the current structural and molecular evidence on microvascular diversity, bioengineering methods used to recapitulate the microenvironmental cues, and recent vascularized three‐dimensional organ models from the perspective of tissue‐specific vasculature.